2018
DOI: 10.1007/s11103-018-0793-y
|View full text |Cite
|
Sign up to set email alerts
|

Transient induction of a subset of ethylene biosynthesis genes is potentially involved in regulation of grapevine bud dormancy release

Abstract: Transient induction of a subset of ethylene biosynthesis genes is potentially involved in regulation of grapevine bud dormancy release

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 66 publications
(82 reference statements)
1
24
0
Order By: Relevance
“…(iii) Hypoxic conditions induce dormancy release (Vergara et al, 2012;Zheng et al, 2015). (iv) Transient increases in ethylene biosynthesis prior to dormancy release support a role for ethylene in activation of dormancy release (Ophir et al, 2009;Shi et al, 2018). In agreement, treatment with exogenous ethylene stimulates dormancy release, whereas treatment with inhibitors of ethylene biosynthesis and ethylene signaling both abolishes dormancy release and antagonizes the enhancing effect of HC/AZ treatments (Ophir et al, 2009;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…(iii) Hypoxic conditions induce dormancy release (Vergara et al, 2012;Zheng et al, 2015). (iv) Transient increases in ethylene biosynthesis prior to dormancy release support a role for ethylene in activation of dormancy release (Ophir et al, 2009;Shi et al, 2018). In agreement, treatment with exogenous ethylene stimulates dormancy release, whereas treatment with inhibitors of ethylene biosynthesis and ethylene signaling both abolishes dormancy release and antagonizes the enhancing effect of HC/AZ treatments (Ophir et al, 2009;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 70%
“…A positive effect of ethylene on the expression of ERF-VIIs has been previously described in rice and in Arabidopsis (Fukao et al, 2006;Hinz et al, 2010). In light of our observations of induction of bud break by treatment with gaseous ethylene (Ophir et al, 2009;Shi et al, 2018), we examined, in our Sealed Vase (SV) system, whether transcription of VvERF057 and VvERF059 might be directly influenced by treatment with ethylene. HC treatment was included as a reference.…”
Section: Ethylene Effects On Expression Of Vverf057 and Vverf059mentioning
confidence: 91%
See 1 more Smart Citation
“…These ethanol treatments may be a promising alternative to cyanamide bud break treatments. The means by which ethanol enhances bud break are not known; however, they may be related to ethylene and oxidative reactions (Shi et al, 2018;Halaly et al, 2008); but validation of these hypotheses requires functional genomic analyses. Further studies of cultivars under differing chilling fulfilment conditions in vineyards and controlled conditions should develop protocols for ethanol use to promote dormancy release in grapevines and other crops.…”
Section: Resultsmentioning
confidence: 99%
“…ACC is the precursor of ethylene in plants, and its conversion to ethylene is known to be associated with the production of hydrogen cyanamide (Lin et al, 2009). Shi et al (2018) showed recently that ethylene production is involved in grapevine bud break. In an earlier study, we showed that spraying ethanol on grapevines generated various responses, including the stimulation of ethylene production (Chervin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%